Muscle Microcirculatory Responses to Incremental Exercises Are Correlated with Peak Oxygen Uptake in Individuals With and Without Type 2 Diabetes Mellitus - Lu Y.J. (2023)
Background: The role of impaired oxygen extraction on peak oxygen uptake (V˙O2peak) has been extensively studied using noninvasive and indirect methods in both diabetic patients and healthy participants. Methods: A total of 22 participants with type 2 diabetes mellitus [T2DM; median (range) age: 60 (47-70) years] and 22 controls [58 (52-69) years] with no history of diabetes were recruited (reference no. 201812135RINB). Subjects performed an exhaustive incremental exercise and were evaluated using a gas analyzer and near-infrared spectroscopy (NIRS) to determine V˙O2peak and changes in muscle oxygenation (SmO2) in the vastus lateralis, respectively. Measurements were taken at rest, warm-up, a period during exercise when SmO2 reached a minimum saturation plateau, and recovery. The microcirculatory responses of the vastus lateralis muscle during incremental exercise in patients with T2DM were compared with those in control individuals, and the correlation between changes in SmO2 and V˙O2peak was estimated. Results: The diabetic group demonstrated lower V˙O2peak, peak workload, peak heart rate, peak minute ventilation (all P < 0.05), and lower SmO2 during the rest, warm-up, and recovery phases (all P < 0.05) compared with the control group. A correlation was observed between the change in SmO2 between the warm-up and plateau value and the V˙O2peak (r = 0.608, P = 0.006). Conclusions: The results obtained in this study using NIRS support the feasibility of directly measuring changes in muscle SmO2 magnitudes to estimate the contributions of peripheral active muscle to systemic O2 uptake (V˙O2) during incremental exercise.